HUBUNGAN ADVERSITY QUOTIENT DENGAN STRES KERJA KARYAWAN PRODUKSI DI PT. X BOGOR - BEATITUDO, EWALDUS SENARAI; FAHLEVI, REZA; BASARIA, DEBORA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The purpose of this research is to determine the relationship between the adversity quotient and work stress among PT production employees. X in Bogor. Method: This research uses quantitative research with regression analysis techniques in the SPSS Statistics 25 application. The sample for this research is 72 production employees. The first measuring instrument used was an adaptation of the new job stress scale. The adaptation was carried out to translate the items on the original measuring instrument so that they could be understood by production employees. The second measuring tool used is a modification of the adversity quotient scale. Results: normality test using the Kolmogorov-Smirnov test showed that work stress data was not normally distributed, p value 0.038<0.05 and the adversity quotient was normally distributed p value 0.097>0.05. The output results were 11 in production employees who experienced low work stress or 15.3%, there were 49 production employees who experienced moderate stress or 68.1% and 12 production employees who experienced high stress or 16.7%. The output results showed that there were 10 employees who had low AQ or 13.9%, there were 49 production employees who had medium AQ or 68.1% and 13 production employees who had high AQ or 18.1%. Based on the results of the Spearman's rho statistical test on work stress, a correlation coefficient value of 1,000 was obtained with a significant value of 0.000 (0.000<0.05). The adversity quotient results obtained a correlation coefficient value of 0.688 with a significant value of 0.000 (0.000<0.05). Statistical test results show that there is a relationship between the two variables, namely a positive relationship. Positive correlation is the relationship between two variables that move in the same direction. Therefore, one variable increases if the other variable also increases. Aspects that can support this positive relationship are control, origin-owner, reach and endurance. ABSTRAKTujuan penelitian ini untuk mengetahui hubungan adversity quotient dengan stres kerja dengan karyawan produksi PT. X di bogor. Metode: penelitian ini menggunakan jenis penelitian kuantitatif dengan teknik analisis regresi pada aplikasi SPSS Statistics 25. Sampel penelitian ini berjumlah 72 orang karyawan produksi. Alat ukur pertama yang digunakan adalah adaptasi dari the new job stress scale, adaptasi dilakukan untuk menerjemahkan butir-butir alat ukur asli sehingga dapat dipahami oleh karyawan produksi. Alat ukur kedua yang digunakan adalah modifikasi dari Skala adversity quotient. Hasil: uji normalitas dengan kolmogorov-smirnov test didapatkan data stress kerja tidak berdistribusi normal p value 0,038<0,05 dan adversity quotient berdistribusi normal p value 0,097>0,05. Hasil output 11 pada karyawan produksi yang mengalami stres kerja rendah atau 15.3%, terdapat 49 karyawan produksi yang mengalami stres sedang atau 68.1% dan 12 karyawan produksi yang mengalami stres tinggi atau 16.7%. Hasil output terdapat 10 karyawan yang memiliki AQ rendah atau 13.9%, terdapat 49 karyawan produksi yang memiliki AQ sedang atau 68.1% dan 13 karyawan produksi yang memiliki AQ tinggi atau 18.1%. Berdasarkan hasil uji statistic Spearman’s rho pada stress kerja diperoleh nilai correlation coefficient 1.000 dengan nilai signifikan 0,000 (0,000<0,05). Hasil adversity quotient diperoleh nilai correlation coefficient 0,688 dengan nilai signifikan 0,000 (0,000<0,05). Hasil uji Statistic menunjukkan bahwa terdapat hubungan antara kedua variabel yaitu hubungan positif. Korelasi positif adalah hubungan antara dua variabel itu bergerak dalam arah yang sama. Oleh karenanya, satu variabel meningkat jika variabel lainnya juga meningkat. Aspek yang dapat mendukung terjadinya hubungan positif ini adalah control, origin-owner, reach dan endurance.